Les Agences de l’eau et la restauration : 50 ans de tensions entre hydraulique et écologique - Bertrand Morandi; Hervé Piégay; Karen Johnstone; Diego Miralles (VertigO)
River restoration paradigm takes a major place in French current management of water and aquatic environments. The paradigm signifiance becames more complex for the late 1970s and its first scientific and operational occurrences. Interest for restoration has not declined but its objectives are still discussed. Especially, meanings of restoration, rehabilitation and renaturation concepts also changed without clear established definitions and practices. Focused on French Water Agencies (FWA) Loire-Bretagne, Rhin-Meuse and Rhône-Méditerranée-Corse, this research is a retrospective study of intervention policies in the field of river restoration. Main objective of the research is to highlight geographical and historical differences in definitions and practices of river restoration in French public policies. The research is based on qualitative analysis of Intervention Programs on these basins (1964-2018). In addition to this analysis we performed a quantitative content analysis of financial aids granted by the FWA to achieve river restorations (1997-2011). The results underline a tension between hydraulic and ecological conceptions of restoration. This tension is still real despite the diversification and hybidization of practices. The present analysis of AE policy interventions can contribute to the current debate about a possible rise of river restorations in public action.